2020
DOI: 10.1029/2019gl085694
|View full text |Cite
|
Sign up to set email alerts
|

Advective Fluxes in the Martian Regolith as a Mechanism Driving Methane and Other Trace Gas Emissions to the Atmosphere

Abstract: Advective fluxes influence methane and CO2 soil emissions into the atmosphere on Earth and may drive trace gas emissions in the Mars atmosphere. However, their relevance in the Martian regolith has not been evaluated to date. Our regolith transport simulations show that advective fluxes can be relevant under Martian conditions and may drive the methane abundance detected by Mars Science Laboratory. Trace gas emissions would be highest in regions where winds interact with topography. Emissions in these regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The daytime absence of methane recorded by TLS-SAM, and the new additional nighttime values reported here, are a critical update to the Curiosity data set to constrain the possible mechanisms of methane production and removal on Mars and are a step toward reconciling the apparent differences between this data set and that of the TGO. Building upon the models of Moores et al (2019b,a), Viúdez-Moreiras et al (2020), Pla-Garcia et al (2019, and of Etiope & Oehler (2019), the TLS-SAM data provide evidence for methane production from a near-surface source, most likely from continuous micro-seepage, that is temporarily contained in the near-surface atmosphere during the night due to the low planetary boundary layer, reduced atmospheric mixing, and horizontal transport. Increased atmospheric dynamics during the daytime mixes the gas accumulated in the night into the global atmosphere where it is diluted to the very low levels constrained by the TGO nondetection.…”
Section: Below and Inmentioning
confidence: 67%
See 2 more Smart Citations
“…The daytime absence of methane recorded by TLS-SAM, and the new additional nighttime values reported here, are a critical update to the Curiosity data set to constrain the possible mechanisms of methane production and removal on Mars and are a step toward reconciling the apparent differences between this data set and that of the TGO. Building upon the models of Moores et al (2019b,a), Viúdez-Moreiras et al (2020), Pla-Garcia et al (2019, and of Etiope & Oehler (2019), the TLS-SAM data provide evidence for methane production from a near-surface source, most likely from continuous micro-seepage, that is temporarily contained in the near-surface atmosphere during the night due to the low planetary boundary layer, reduced atmospheric mixing, and horizontal transport. Increased atmospheric dynamics during the daytime mixes the gas accumulated in the night into the global atmosphere where it is diluted to the very low levels constrained by the TGO nondetection.…”
Section: Below and Inmentioning
confidence: 67%
“…The release of methane to the atmosphere by means of seepage should also be strongly affected by winds and pressure fluctuations. Model simulations suggest that advective fluxes produced by winds have strong relevance on regolith emissions under Martian conditions in highly permeable soils such as fracture media (Viúdez-Moreiras et al 2020). A potential seasonal variation in the methane background levels is also indicated by a numerical model considering wind-dependent methane emissions in Aeolis Mons and in other crater locations (Viúdez-Moreiras et al 2020).…”
Section: Below and Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, this work presents a case study involving the simulation of methane spikes detected by NASA's Mars Science Laboratory (MSL), which have been attributed to surface emissions in the vicinity of the MSL (Webster et al 2015;Webster et al 2018). Methane on Mars represents a puzzle in that there is not a satisfactory explanation of its origin, source locations, and detected variability (e.g., Yung et al 2018;Moores et al 2019;Viúdez-Moreiras et al 2020a), including apparent mismatches among observations (e.g., Webster et al 2015;Webster et al 2018;Korablev et al 2019), and it is therefore a potential application for DISVERMAR.…”
Section: Introductionmentioning
confidence: 99%
“…Viúdez‐Moreiras, Arvidson, et al. (2020) suggested that the methane abundance detected by MSL could be significantly influenced by local meteorology and/or that methane source emissions could be highly dependent on location, areocentric solar longitude (L s ), and local time.…”
Section: Introductionmentioning
confidence: 99%